The Seventh-Day Adventist Attitudes Towards Polygamy In Africa: A Nigerian Context (Journal of Namibian Studies : History Politics Culture, 2023)
The attitudes of the foreign missionaries in converting the indigenous people into Christianity in Africa, especially in Nigeria, implied denying polygamists and household of their faith and salvation in Christ Jesus. The non-Seventh-day Adventist (non-SDA) Christian missionaries and the SDA missionaries put forward monogamy as the basis for conversion in their missiological enterprise which opposes polygamy. Though the SDA missionaries turned ‘deaf ear’ to people’s queries on the church’s official position and imposed their faith, there are still the presences of polygamists in the church. Based on this background, this paper therefore examines why the presence of polygamists in the church if not that the SDA missionaries ‘attitudes must have tilted toward another trend other than the official position using a qualitative method focalizing analytical approach. This paper finds, among others, that the attitudes of the SDA missionaries, having asked polygamists to drop other wives, appeared hard, harsh, and racial yet polygamists are in the church. This study, among others, suggests that the SDA missionaries’ attitudes should rather be characterized by love as it would not only influence positively the faith of the wives, that would have been dropped, but of their children, particularly, by according them the opportunity to grow in Christ onto maturity with others in the church.